Straddling two worlds: How academic literacy can inform discipline-specific teaching - Yoo, Joanne (Journal of Academic Language and Learning, 2016)
Academic literacy and discipline specific teaching have often been separated in Australian higher education settings, where academic skills advisors facilitate academic literacy skills whilst disciplinary specific academics deliver content area knowledge and skills. This superficial separation has often created situations where academic literacy advisors have had to address student learning issues without a clear understanding of subject specific knowledge and assessment requirements. The current article explores the greater integration of the teaching of academic skills and content area knowledge through an autoethnography, in which two professional roles merge. This study documents an advisor’s attempts to use writing activities to scaffold discipline specific teaching within a Bachelor of Primary Teacher Education subject at the University of Technology, Sydney (UTS). It illustrates how academic advisors acquire a unique insight into effective teaching strategies as they directly address students’ learning needs.